Результати експериментальних досліджень точності визначення координат та практичне застосування RTK-технології з використанням GPRS Internet з’єднання - Задемленюк, Антоніна (Видавництво Національного університету «Львівська політехніка», 2009)
In articles results experimental work through technologies of precision positioning with use of method RTK are resulted. The opportunity of reception of a entimetric level of accuracy of positioning on distance up to 70 km from base GNSS-station is shown. Results of the analysis of the received coordinate determinations in a real-time mode are submitted in comparison with the data postprocessings.
Keywords: RTK-технологія; GPRS; GNSS-технології; EPN